THE IMPOSITION OF COMMON LAW IN THE INTERPRETATION AND APPLICATION OF CUSTOMARY LAW AND CUSTOMARY MARRIAGES (The Pretoria Student Law Review, 2021)
South Africa has, over the past few years, seen the development of its jurisprudence in respect of the interpretation and application of African customary law under the new constitutional dispensation as it now also forms an integral part of South African law. Our courts are, in terms of the Constitution, required to apply African customary law when it is applicable, but like any other law, it is also subject to the Constitution. It is also submitted that due to the repercussions of the past, African customary law and laws regulating customary marriages are yet to reach their proper development, and this slow development is also caused by inconsistencies and the imposition of common law in the interpretation and application of African customary law and laws regulating customary marriages. Furthermore, African customary law should not be hinged on what colonisation bequeathed us, as the interpretation of our customary law through the prisms of common law frustrates the development of customary law — which has for a long time been prevented from developing securely alongside common law.
Keywords: common law; African customary marriages; common law development; Constitution